Makers of a nation : Kungu Karumba / the men and women in Kenya s history. (Nairobi : NTV, 2010)
This is the story of the life and times of Kungu Karumba, one of six legendary Mau Mau freedom fighters, including Jomo Kenyatta, whom the British colonial authorities arrested and tried in a hastily made up court in a small town in north-western Kenya called Kapenguria, convicted and locked up in jail and detention for nearly a decade before the country s independence.
Summary from container.
Viewed for credits and content.
Source used: videodisc container.
Editor, Nick Nderitu ; production coordinator, Alice Kageni ; researcher, Dishon Shangalla ; production assistant, Mercelline Maroma ; audio recording, Davis Mwasaru ; cameramen, James Opiyo, Alfred Chomba, Geofrey Guantai ; executive producers, Wangethi Mwangi, Conrad Nkutu.
Narrator: Lorna Dias.
Keywords: Political activists; Political prisoners; Mau Mau; Karumba, K ungu, -- 1902-1974?; Biography. -- Kenya; Kenya